Green roofs in the tropics: design considerations and vegetation dynamics - Iana F. Grullón – Penkova; Jess K. Zimmerman; Grizelle González (Heliyon, 2020)
Green roofs (GR) have been proposed as a possible solution for urban stressors that, integrated with other remediation and mitigation actions, can lead the way to a more sustainable society. Even when some aspects of green roof design are well established and known (i.e. depth arrangements, materials, structural components, etc.) there is a need for further development on ecological attributes. This study is a descriptive analysis of suitable plant species for their possible incorporation in green roof designs with tropical climate conditions. Green roof research has been mostly led by temperate climate countries and has neglected to address tropical areas; this study aims to move research towards this knowledge gap. The evaluation of the vegetation dynamics in these novel ecosystems was done through a case study in the renovated facilities of the International Institute of Tropical Forestry in Río Piedras, Puerto Rico, which incorporated a set of green roofs in their infrastructure. We also sampled an older green roof built in the Social Sciences Faculty at the University of Puerto Rico at Río Piedras. A three-dimensional approach, the Point-Intercept Method, was taken in the vegetation surveys to capture as much as possible the green infrastructure of the roofs. Most of the originally planted species did not appear in these surveys. On the contrary, mainly new species dominated the areas. Along with the findings of these surveys and those in other tropical countries, a list of suitable species for green roofs in Puerto Rico is suggested, and some general recommendations are made for the better management of green roofs in tropical zones.